The Form of Rejection Language by English Lecturer in Teaching Learning Process at Cokroaminoto Palopo University - Tsamratul'aeni Tsamratul'aeni (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2021)
This research aims at finding out the forms of rejection language used of English lecturer in teaching learning process. This research used descriptive qualitative method. The population in this research was English lecturer that consist of two lecturers and the researcher took the lecturers totally as the sample. The instrument of this research were observation and interview. The results of the data analysis explained that two major finding. First, in this research is she found that the forms of rejection language used of English lecturers. Second is the researcher revealed that the reason of English lecturer used rejection language. The researcher found that the most used English lecturers in learning process were rejection language in the form of declarative speech. It is shown from finding that all of the rejection language that used of English lecturers were 12 utterances where rejection language in the form of declarative speech were 5, the rejection language in the form of imperative speech were 5 and the rejection language in the form of interrogative speech. So, the researcher concludes that the English lecturers more like used rejection language in the form of declarative speech. It was caused that the rejection language has big influence to the activity of students in teaching learning process.